A paleofauna do conjunto de afloramentos Niemeyer (Triássico Superior do Sul do Brasil) e seu contexto bioestratigráfico - Doering, Mariana (2025)
Biostratigraphic proposals are essential for outcrops that lack an absolute age. This is the condition of the the Niemeyer Complex, located in the municipality of Agudo, Rio Grande do Sul. Since its discovery, numerous fossil specimens have been found in the locality, but none are typical of any known Assemblages Zones (AZ) for the Brazilian Triassic, making precise date difficult. Furthermore, the Niemeyer Complex consists of two distinct portions (lower and upper), each showing differences in lithological and fossil content. Over the years, Brazilian biostratigraphy has become increasingly complex due to extensive fieldwork, the description of new species, and the discovery of new fossil sites. Between 2014 and 2024, new materials were discovered for both portions of the Niemeyer Complex, particularly for the lower portion, which had previously been restricted to fragmentary specimens. All materials were mechanically prepared and phylogenetic analyses were conducted on some specimens. Based on the new findings, it was possible to infer a Carnian age for the lower portion, as the specimens from this layer are characteristic of the fauna found in the Hyperodapedon AZ, such as dinosaurs, lagerpetids, cynodonts and rhynchosaurs of the genus Hyperodapedon. In contrast, the upper portion contains different specimens that those found in the lower layers, suggesting an age closer to the beginning of the Norian. This is supported by the presence of more derived dinosaurs than those typical of Carnian, and the rhynchosaur Teyumbaita sulcognathus, which has been found in higher layers in both Argentine and Brazilian outcrops above those containing Hyperodapedon. These results enrich our understanding of the paleofauna of the Niemeyer Complex and expand our knowledge of the diversity of species present in the different strata of the Candelária Sequence.